Blood flow velocity in monocular retinoblastoma assessed by color doppler - Maria Teresa B.C. Bonanomi; Osmar C. Saito; Patricia Picciarelli de Lima; Roberta Chizzotti Bonanomi; Maria Cristina Chammas (Clinics, 2015)
OBJECTIVE: To analyze the flow of retrobulbar vessels in retinoblastoma by color Doppler imaging. METHODS: A prospective study of monocular retinoblastoma treated by enucleation between 2010 and 2014. The examination comprised fundoscopy, magnetic resonance imaging, ultrasonography and color Doppler imaging. The peak blood velocities in the central retinal artery and central retinal vein of tumor-containing eyes (tuCRAv and tuCRVv, respectively) were assessed. The velocities were compared with those for normal eyes (nlCRAv and nlCRVv) and correlated with clinical and pathological findings. Tumor dimensions in the pathological sections were compared with those in magnetic resonance imaging and ultrasonography and were correlated with tuCRAv and tuCRVv. In tumor-containing eyes, the resistivity index in the central retinal artery and the pulse index in the central retinal vein were studied in relation to all variables. RESULTS: Eighteen patients were included. Comparisons between tuCRAv and nlCRAv and between tuCRVv and nlCRVv revealed higher velocities in tumor-containing eyes (p <0.001 for both), with a greater effect in the central retinal artery than in the central retinal vein (p =0.024). Magnetic resonance imaging and ultrasonography measurements were as reliable as pathology assessments (p =0.675 and p =0.375, respectively). A positive relationship was found between tuCRAv and the tumor volume (p =0.027). The pulse index in the central retinal vein was lower in male patients (p =0.017) and in eyes with optic nerve invasion (p =0.0088). CONCLUSIONS: TuCRAv and tuCRVv are higher in tumor-containing eyes than in normal eyes. Magnetic resonance imaging and ultrasonography measurements are reliable. The tumor volume is correlated with a higher tuCRAv and a reduced pulse in the central retinal vein is correlated with male sex and optic nerve invasion.